Effectiveness SPEOS Method (Endorphin, Oxytocin, and Suggestive Massage Stimulation) on Breast Milk Production in Postpartum Mothers: A Systematic Literature Review - Puspitasari, Dhita; Setyowati Esti Rahayu, Heni; Wijayanti, Kartika; Rohmayanti (Gaster, 2025)
Background The postpartum period is a critical phase of physiological and psychological recovery, beginning with the expulsion of the placenta and typically lasting up to six weeks. Breast milk (human milk) is recognized as the most essential source of nutrition for newborns, particularly in the first month of life. Various interventions have been explored to enhance lactation, one is the SPEOS method—a non-pharmacological approach combining endorphin stimulation, oxytocin release, and suggestive massage. Beyond physical aspects, maternal psychological adaptation also plays a vital role in successful breastfeeding. Objective This study aimed to evaluate the effectiveness of the SPEOS method in stimulating breast milk production among postpartum mothers through a literature review approach. Methods A literature review design was employed by analyzing relevant studies from national and international databases. Articles were selected based on predetermined inclusion criteria, and data synthesis focused on outcomes related to breast milk production following the application of the SPEOS method. Results The reviewed studies consistently reported a statistically significant effect of the SPEOS method on increasing breast milk production among postpartum women. The average reported p-value across the studies was 0.000, indicating a high level of statistical significance. Conclusion The SPEOS method appears to be an effective non-pharmacological intervention to enhance breast milk production in postpartum mothers. Further empirical research with standardized protocols is recommended to strengthen the evidence base and explore long-term outcomes.